PENGARUH BUDAYA KERJA, KEMAMPUAN KERJA, TEAM WORK DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MEDAN - Fakhrulsyah Mega; Dewi Ratna Bulan Siregar; Dana Syah Putra; Heru Pramana; As Ari (Universitas Islam Islam Sumatera Utara, 2021)
Problem of this study what is influence of job culture on performance. What is influence of work ability on performance. What is influence of team work on performance. What is influence of job motivation on performance. What is influence job culture, work ability, team work and job motivation on performance. The purpose of this study to determine and analyze the effect of job culture on performance. Determine and analyze the effect of work ability on performance. Determine and analyze the effect of team work on performance. Determine and analyze the effect of job motivation on performance. Determine and analyze the effect of job culture, work ability, team work and job motivation on performance. Sample in the study is 60 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job culture has a positive and significant effect on performance. Work ability has a positive and significant effect on performance. Team work has a positive and significant effect on performance. Job motivation has a positive and significant effect on performance. Job culture, work ability, team work and job motivation has a positive and significant effect on performance.